Developing a multivariate drought index to assess drought characteristics based on the SWAT-Copula method in the Poyang Lake basin, China - Liping Guo; Fusheng Chen; Bin Wang; De Li Liu; Xiulong Chen; Hongsheng Huang; Hua Bai; Kaitao Liao; Zhiming Xia; Keyu Xiang; Linchao Li; Taihui Zheng; et al. (Ecological Indicators, 2025)
The Poyang Lake Basin (PLB) has a long-standing history of drought, which has been intensified by global warming, posing significant risks to water security and agriculture. However, the specific patterns of drought, particularly seasonal variations, remain poorly understood, making it crucial to investigate these dynamics for effective water management and resilience planning. We employed calibrated SWAT model to simulate monthly soil moisture in five sub-basins to analyze drought characteristics across the PLB over the past six decades. A Multivariate Standardized Drought Index (MSDI) was then developed with simulated Standardized Soil Moisture Index (SSI) and Standardized Precipitation Index (SPI) based on copula functions. We found that (1) The SWAT can simulate monthly streamflow well with NS being 0.76–0.92 for validation data over the sub-basins in the PLB. (2) The MSDI index indicated that there were more drought events during 1960–1979 and 2000–2019, highlighting a cyclical pattern of drought events in the PLB. (3) The Xiushui River Basin encountered the most extreme drought conditions since 2000, indicating the basin faced a high risk of dry conditions. Additionally, our wavelet period analysis showed an increase in drought frequency after the year 2000, with less distinct periodicity. These findings contribute to our understanding of drought dynamics in the Poyang Lake Basin and offer valuable insights for developing sustainable water resource management and climate adaptation strategies in the region.